2013
DOI: 10.3389/fnhum.2013.00803
|View full text |Cite
|
Sign up to set email alerts
|

Long-range neural activity evoked by premotor cortex stimulation: a TMS/EEG co-registration study

Abstract: The premotor cortex is one of the fundamental structures composing the neural networks of the human brain. It is implicated in many behaviors and cognitive tasks, ranging from movement to attention and eye-related activity. Therefore, neural circuits that are related to premotor cortex have been studied to clarify their connectivity and/or role in different tasks. In the present work, we aimed to investigate the propagation of the neural activity evoked in the dorsal premotor cortex using transcranial magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 121 publications
2
12
0
Order By: Relevance
“…Alongside the described local effects of sTMS and rTMS, we found that TMS can enhance population-level measures of phase-amplitude coupling over various other cortical sites. In line with this finding, propagation of neural activation related to either sTMS or rTMS has been shown in a number of previous studies [13,14,[49][50][51][52][53][54]. In particular, should follow the brain's intrinsic organizational structure, which is characterized by frequency-specific functional networks [55].…”
Section: Discussionsupporting
confidence: 70%
“…Alongside the described local effects of sTMS and rTMS, we found that TMS can enhance population-level measures of phase-amplitude coupling over various other cortical sites. In line with this finding, propagation of neural activation related to either sTMS or rTMS has been shown in a number of previous studies [13,14,[49][50][51][52][53][54]. In particular, should follow the brain's intrinsic organizational structure, which is characterized by frequency-specific functional networks [55].…”
Section: Discussionsupporting
confidence: 70%
“…Both dPMCs are involved in motor learning in healthy subjects and stroke patients (Stagg and Johansen-Berg, 2013;Stefan et al, 2008;Stinear et al, 2009;Wang et al, 2014;Zanon et al, 2013). We are already aware of the involvement of the underlying network in hand motor training in a mirror (mirror training, MT): In an fMRI study we found higher effective connectivity between both dPMCs with the supplementary motor area (SMA) and M1 left when the right hand was trained in a mirror (Hamzei et al, 2012b).…”
Section: Introductionmentioning
confidence: 82%
“…In healthy adults, TMS of the frontal cortex elicits a waveform showing several TEP components and lasting at least up to 300 ms (Massimini et al, ; Rogasch et al, ; Rogasch, Daskalakis, & Fitzgerald, ). Both the dorsolateral frontal cortex (Cash et al, ; Fitzgerald et al, ; Kähkönen et al, ; Lioumis, Kicic, Savolainen, Mäkelä, & Kähkönen, ; Rogasch et al, ) and superior frontal cortex or premotor area (Casarotto et al, ; Ferrarelli et al, ; Massimini et al, ; Zanon, Battaglini, Jarmolowska, Pizzolato, & Busan, ) have been targeted. Despite this methodological difference, a sequence containing deflections (named after their latency and polarity; N = negative, P = positive) at around 30 ms (P30), 40–50 ms (N45), 60 ms (P60), 100–120 ms (N100), and 160–190 ms (P180) is frequently reported in response to frontal cortex stimulation (Kähkönen, Komssi, Wilenius, & Ilmoniemi, ; Lioumis et al, ; Noda et al, ; Rogasch et al, ).…”
Section: Introductionmentioning
confidence: 99%